PELAYANAN FASILITAS TERMINAL BAGI PENGGUNA JASA PENERBANGAN - Indra Yuzal; Adi Wiratama (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2016)
PT. Angkasa Pura I is the services provider for flights and non-aeronautica in Indonesia. The researcher is using quantitative and simple linear regression analysis (Sugiyono, 20018: 272) to find out the effect of terminal facilities services for the passengers. The result shows that there is an effect of terminal facilities services for the passengers in Husein Sastranegara airport from March to May 2014. The –t count > -t table (5.177 > 1.833) which means Ho is rejected. If Ho is rejected, then there is a significant effect between the services quality to the passengers.